2022
DOI: 10.3390/land11122251
|View full text |Cite
|
Sign up to set email alerts
|

Concatenating Daily Exercise Routes with Public Sports Facilities, Bicycle Lanes, and Green Spaces: A Feasibility Analysis in Nanjing, China

Abstract: Public sports facilities have the potential to improve their functions as active living infrastructures (ALIs) in combination with bicycle lanes and green spaces. A favorable sequence of exercise intensities in different scenes is important for individuals to take physical activity scientifically. Our research aimed to explore the feasibility of promoting and consolidating this sequence using reasonable daily exercise routes concatenated by public sports facilities, green spaces, and bicycle lanes. Taking 25 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 46 publications
0
2
0
3
Order By: Relevance
“…Na 3ª fase foram excluídos mais 7 estudos: 4 com "conceito de vida ativa", 1 com "active life concept" e 2 com "active life meaning", permanecendo 9 estudos. Após a 4ª etapa foram excluídos 7 estudos: 4 para "conceito de vida ativa", 2 para "active life concept" e 1 para "active life meaning", resultando 2 estudos - ONOFRE, 2017;CHEN et al, 2022 -para compor a presente pesquisa. A Figura 1 apresenta um fluxograma com as etapas do processo de busca e seleção dos estudos.…”
Section: Resultsunclassified
See 2 more Smart Citations
“…Na 3ª fase foram excluídos mais 7 estudos: 4 com "conceito de vida ativa", 1 com "active life concept" e 2 com "active life meaning", permanecendo 9 estudos. Após a 4ª etapa foram excluídos 7 estudos: 4 para "conceito de vida ativa", 2 para "active life concept" e 1 para "active life meaning", resultando 2 estudos - ONOFRE, 2017;CHEN et al, 2022 -para compor a presente pesquisa. A Figura 1 apresenta um fluxograma com as etapas do processo de busca e seleção dos estudos.…”
Section: Resultsunclassified
“…Os conceitos de vida ativa apresentados nos estudos selecionados (ONO-FRE, 2017;CHEN et al, 2022) revelam que a definição de vida ativa está relacionada ao envolvimento com a prática de atividades físicas e esportivas. Onofre (2017) ao se referir a indicadores sobre a vida ativa das populações dos países do sul e leste europeu, mostra dados que estão relacionados à prevalência da prática de atividade física e desportiva, com destaque para evidências que revelam a inexistência de hábitos regulares (EUROPEAN COMISSION, 2014;MARQUES et al, 2014).…”
Section: Discussionunclassified
See 1 more Smart Citation
“…(4) Traffic data were obtained through Baidu's open map platform, (https://lbsyun.baidu. com/, accessed on 27 March 2022), which could be divided into static and dynamic data [76]. Static data encompassed the latitude, longitude, and names of subway stations and bus stations.…”
Section: Datamentioning
confidence: 99%
“…Most of the studies concluded that a spatial imbalance of sports and fitness facilities still exists in different regions of China, the supply of sports facilities fails to match the demand of residents, and the accessibility of sports facilities in central urban areas is significantly better than that in suburban and rural areas [ [20] , [21] , [22] ]. In addition, Lee et al noted that the convenience of accessing and using sports and fitness resources can effectively enhance residents' willingness to participate in physical exercise and thereby enhance their sense of access [ 23 ]. Therefore, it is necessary and meaningful to pay attention to issues such as the balance and accessibility of the spatial distribution of national fitness resources.…”
Section: Literature Reviewmentioning
confidence: 99%